Cyber security Risks in DBMS: Strategies to Mitigate Data Security Threats: A Systematic Review - Muzammal Farooq; Rana M. Faheem Younas; Junaid Nasir Qureshi; Ali Haider; Fawad Nasim (Spectrum of Engineering Sciences, 2025)
Database systems have been prime targets for cyber-attacks and threats due to the critical nature of the data they store. Despite the increasing reliance on database management systems, this field continues to face numerous cyber-attacks. Databases are collections of well-organized data that can be accessed, maintained, and updated quickly. Database systems are critical to your company because they convey data about sales transactions, product inventories, customer profiles, and marketing activities. The number of attacks against these repositories has also increased. Increasing internet consumption and constant technological development, specifically have led to an increasingly urgent need for cyber awareness. Database Management Systems (DBMS) are the backbone of modern organizations, enabling efficient storage and retrieval of sensitive information. However, as the digital landscape evolves, so do the cybersecurity risks targeting these systems. This paper critically reviews existing research to identify key cybersecurity threats to DBMS, including SQL injection, ransomware, insider threats, and denial-of-service attacks. The paper analyzes recent studies and explores advanced strategies for mitigating these threats, such as AI-driven anomaly detection, blockchain-based security models, and Zero Trust architectures. The objective is to provide a clear understanding of the risks and actionable insights into building robust, secure database systems. This study offers a comprehensive analysis aimed at helping researchers and practitioners develop effective data security measures, ensuring both resilience and adaptability in an increasingly hostile cyber environment. Keywords: Cyber insurance, Cyber risk, Open data, Systematic review, DBMS, database security threat mitigation, Data protection strategies for DBMS, Cyber threats in database management, DBMS cybersecurity challenges